The housing provision system in Malaysia - Shuid, Syafiee (Elsevier Ltd., 2016)
Since Habitat I in 1976, the housing provision system in Malaysia have gone through various phases to keep pace with country's political economy changes and globalization as promoted by the international agencies such as the World Bank and International Monetary Fund (IMF). Malaysia have made tremendous progress to address severe housing shortage, substandard housing and slums in the urban areas since independence in 1957. The Structure of Housing Provision (SHP) framework will be used to analyze the changes of housing provision system in Malaysia since 1970s. The housing provision in Malaysia since 1971 can be divided into four phases namely Housing the Poor (1971e1985), Market Reform (1986e1997), Slums Clearance (1998e2011) and State Affordable Housing (2012-to date). Unique country's population and economic background require different approach of policy and programs to address housing problems. Nevertheless the state and market continue to play an important role in housing provision since 1970s regardless of country's political economic changes. As a result more than 1.3 million low cost housing units has been built by both private and public sector from 1971 to 2010 to address housing need for the poor throughout the country and reduced significantly the number of people lived in slums. To address housing need for growing middle income group and changing people lifestyle another 1 million of affordable housing units are planned to be built in the next 5 years until 2020 mainly through the state affordable housing programs. Finally, the paper also will highlight the challenges and problems faced by the state and market in the implementation of various housing pro- grams in Malaysia since Habitat I.